Backward Weighted Coding - Fruchtman, Aharon; Gross, Yoav; Klein, Shmuel T.; Shapira, Dana (DCC (Los Alamitos, Calif.), 2021)
Extending recently suggested methods, a new dynamic compression algorithm is proposed, which assigns larger weights to characters that have just been coded by means of an increasing weight function. Empirical results present its efficient compression performance, which, for input files with locally skewed distributions, can improve beyond the lower bound given by the entropy for static encoding, at the price of slower running times for compression, and comparable time for decompression.